Analysis and Optimization Study of Antenna Selection in Dual Hop Relay Networks over Weibull Fading Channels - Erdogan, Eylem; Gucluoglu, Tansal (SPRINGER, 2018)
Field experiments show that Weibull distribution can be considered as the most suitable distribution to model weak to high signal power levels in indoor and outdoor environments. Recently, Exponentiated Weibull which is a special case of Weibull fading, have been widely adopted in free-space optical communication systems to model weak and high levels of turbulence effects. Motivated from the increasing use of Weibull distribution, this paper studies the popular dual-hop amplify-and-forward relay network with joint transmit and receive antenna selection where closed form ergodic capacity, symbol error rate and outage probability expressions are derived for Weibull fading channels. With the help of high SNR analysis, diversity gain, array gain and optimum relay location are obtained. Finally, theoretical findings are validated by simulation results.
Keywords: Cooperative communication; Antenna selection; Weibull fading channel; Performance analysis; WIRELESS NETWORKS; UNIFIED ANALYSIS; DIVERSITY; PROBABILITY; PERFORMANCE; Telecommunications